2002
DOI: 10.2169/internalmedicine.41.709
|View full text |Cite
|
Sign up to set email alerts
|

SP-D as a Marker of Amiodarone-induced Pulmonary Toxicity.

Abstract: Twopatients with amiodarone-induced pulmonary toxicity (APT) showed abnormally increased serum SP-D concentrations, although their KL-6 level was within the normal range. In a 59-year-old man with ischemic heart disease, APTprogressed rapidly and required steroid pulse therapy. During the clinical course, SP-D was as high as 375 ng/ml, although the KL-6 level was only 289 U/ml. In a 58-year-old man treated for dilated cardiomyopathy, SP-D increased to 289 ng/ml, while KL-6 remained at less than 500 U/ml. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Koopmans et al show here not only that baseline serum SP‐D in allergic patients was significantly elevated in comparison with controls but also, that serum SP‐D level appeared to be an independent predictor for the magnitude of the late asthmatic response and sputum eosinophilic cationic protein (ECP) concentration after allergen challenge. Serum SP‐D levels have been previously shown to be sensitive markers of disease severity in a number of different lung diseases including ABPA [22], community‐acquired pneumonia [23], interstitial lung diseases in patients with polymyositis [24], acute lung injury [25, 26], idiopathic pulmonary fibrosis [27] and hypersensitivity pneumonitis, just to mention a few recent studies. The present work by Koopman's and colleagues is important since it demonstrates that SP‐D is now detectable relatively easily from the serum of asthmatic patients, and it could be useful as a biomarker, sensitive enough to predict the extent of airway inflammation.…”
Section: Surfactant Protein D Is Selectively Induced During the Acutementioning
confidence: 99%
“…Koopmans et al show here not only that baseline serum SP‐D in allergic patients was significantly elevated in comparison with controls but also, that serum SP‐D level appeared to be an independent predictor for the magnitude of the late asthmatic response and sputum eosinophilic cationic protein (ECP) concentration after allergen challenge. Serum SP‐D levels have been previously shown to be sensitive markers of disease severity in a number of different lung diseases including ABPA [22], community‐acquired pneumonia [23], interstitial lung diseases in patients with polymyositis [24], acute lung injury [25, 26], idiopathic pulmonary fibrosis [27] and hypersensitivity pneumonitis, just to mention a few recent studies. The present work by Koopman's and colleagues is important since it demonstrates that SP‐D is now detectable relatively easily from the serum of asthmatic patients, and it could be useful as a biomarker, sensitive enough to predict the extent of airway inflammation.…”
Section: Surfactant Protein D Is Selectively Induced During the Acutementioning
confidence: 99%
“…Other factors that influence the serum SP-D level is age, gender and smoking status (Sorensen et al 2006a). Serum SP-D has proven to be a robust marker for pulmonary injury (Miyata et al 2002;Umetani et al 2002), and has thus been suggested used as a prognostic and predictive marker for a multitude of pulmonary inflammatory diseases (reviewed in Hartl and Griese 2006;Sorensen et al 2007). The antimicrobial and antiinflammatory functions of the molecule indicate that fluctuations in the molecular levels may affect the disease outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Mice that lack SP-D develop chronic inflammation and emphysema that can be prevented by administration of truncated recombinant human SP-D [8]. Since SP-D is synthesised predominantly within the respiratory tract, it has been evaluated as a potential biomarker in small numbers of individuals with community-acquired pneumonia [9], drug-induced lung disease [10,11], interstitial fibrosis [12] and allergic bronchopulmonary aspergillosis in cystic fibrosis [13]. Levels are reduced in bronchoalveolar lavage fluid from individuals with COPD [14], and there was a weak inverse relationship between serum SP-D level and forced expiratory volume in 1 s (FEV1) in 23 individuals with advanced COPD [15].…”
mentioning
confidence: 99%